PEMBERIAN AIR REBUSAN SELEDRI (Apium graveolens L.) TERHADAP PENURUNAN TEKANAN DARAH LANSIA DENGAN HIPERTENSI - Iswari, Ari (Coping: Community of Publishing in Nursing; Vol 3 No 1 (2015): JURNAL EDISI JANUARI-APRIL 2015, 2015)
The increase of blood pressure is one of the manifestations of cardiovascular organ degeneration in the elderly. One of the non-pharmacological therapies that can lower blood pressure is the administration of Celery’s decoction. Celery contains 3-n-butylpthalida and apigenin which is very helpful to prevent the narrowing of blood vessels and to reduce the high blood pressure. The study aims to determine the provision of the decoction of celery to decrease blood pressure in the elderly in the Public Health Center IV of South Denpasar. The study used a research design of quasy-experimental design with pre-test and post-test of control group. The samples consisted of 30 elderly who were divided into treatment group and control group with simple random sampling. The analysis of the data using non-parametric Mann Whitney test (a = 0.05) which indicates a significant difference between the treatment group and the control group with a significance value of 0.000. Therefore, it can be concluded that the administration of the decoction of celery for the elderly people effected on the blood pressure reduction.
Keywords: Blood pressure, Celery, The elderly